N-Acetylglucosamine Production by Repeated-Batch Fermentation Using Immobilized Semi-Purified Chitinase Enzyme on Agar - Lucia Soedirga; Hardoko Hardoko; Natasha V Widianto (Dept. of Chemical Engineering, Diponegoro University, 2021)
Chitinolytic mold, such as Mucor circinelloidesis can be utilized to produce chitinase enzyme for shrimp shell’s chitin hydrolysis into N-acetylglucosamine (NAG). For that purpose, entrapment of chitinase on agar as a carrier could be an alternative way to improve NAG production. This study aimed to investigate the stability of immobilized semi-purified chitinase on agar for multiple cycles fermentation to produce NAG. In this study, 0.6 mL of semi-purified chitinase enzyme was immobilized into 3% of agar matrices and tested for four fermentation cycles to obtain highest NAG concentration and good enzyme activity. The results indicate that the immobilized chitinase could be used for 6 hours fermentation or three fermentation cycles. The NAG concentration produced after three cycle were 1042.22 ± 16.20 ppm. Besides, the immobilized enzyme was considerably stable up to the third cycles with activity value of about 4.74 U/mL.Keywords: agar; immobilized;NAG; repeated fermentation